Groundwater Potential in the Serang - Tangerang Groundwater Basin Based on the Groundwater Balance Method - Tirtomihardjo, Haryadi; Setiawan, Taat; Putra, Dendi Borneo; Aminuddin, Aminuddin (Badan Geologi, 2024)
Groundwater u in an area, region or groundwater basin (GB) needs to consider various aspects, especially technicalaspects related to the existence and potential availability of groundwater in that unit area. The existence of groundwaterdescribes where groundwater is stored and distributed in an aquifer system, including the dimensions of theaquifer system and its hydraulic properties; meanwhile, groundwater availability includes the quantity and qualityof groundwater in the aquifer system. For the use of groundwater to be carried out sustainably, the balance betweengroundwater availability and groundwater use needs to be maintained within a safe limit, meaning that the use ofgroundwater does not hurt either the condition or the environment of groundwater. The balance between the twowhich is known through the calculation of the groundwater balance provides an overall picture of the components ofgroundwater that enters and the component of groundwater that exits an aquifer system. The calculation results forthe Serang-Tangerang GB groundwater balance show that the discharge of free groundwater utilized in the 2020-2021 period is around 60% of the recharge discharge, so it is in the category between safe and critical. Meanwhile,the use of groundwater in confined aquifer systems during these two periods was greater than the flow rate so it wasincluded in the damaged category